2016
DOI: 10.1021/acs.jpca.6b08945
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Bonding with Phosphine: Evidence for Mulliken Inner Complexes and the Importance of Relaxation Energy

Abstract: Intermolecular halogen bonding in complexes of phosphine and dihalogens has been theoretically investigated using explicitly correlated coupled cluster methods and sym-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 76 publications
1
43
0
Order By: Relevance
“…The amount of this charge transfer is > 0.14 e (computed with M06‐2X/ADZP), much larger than typical value (≪ 0.1 e ) generally observed for weak to medium and strong intermolecular interactions . For this reason, one might wish to classify the MAPbY 3 complexes as Mulliken inner type …”
Section: Discussionmentioning
confidence: 76%
“…The amount of this charge transfer is > 0.14 e (computed with M06‐2X/ADZP), much larger than typical value (≪ 0.1 e ) generally observed for weak to medium and strong intermolecular interactions . For this reason, one might wish to classify the MAPbY 3 complexes as Mulliken inner type …”
Section: Discussionmentioning
confidence: 76%
“…[35] Noncovalent interactions involving pnicogen atoms have been widely studied. [43][44][45][46][47] Some interesting points emerged from a recent theoretical study of halogen bonding in complexes of phosphine H 3 P. [48] It was found that the relative energetic stabilities of these H 3 P complexes with various YZ (Y,Z = halogen) bases, especially in H 3 P…ClF, depended on how the interaction energies were defined and computed. [36][37][38][39][40][41][42] The effect of other types of intermolecular interactions in pnicogen-bonded complexes has also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Factors influencing the structure, energy and properties of pnicogen-bonded complexes, including the nature of the pnicogen atom and substituent effects on the Lewis acid and Lewis base molecular subunits of these complexes, have been obtained from theoretical studies. [48] In the present study, we consider two measures of the interaction energy for our model complexes, one which takes into account the deformation energy (i. e. the energy required to deform the monomer subunits from their equilibrium geometries to the geometries they adopt in the optimized complex) and one which does not. [43][44][45][46][47] Some interesting points emerged from a recent theoretical study of halogen bonding in complexes of phosphine H 3 P. [48] It was found that the relative energetic stabilities of these H 3 P complexes with various YZ (Y,Z = halogen) bases, especially in H 3 P…ClF, depended on how the interaction energies were defined and computed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the charge transfer interaction is more important in the Te···X halogen bond. It should be mentioned that halogen‐bonded complexes have been classified as charge‐transfer complexes in previous studies . The large charge transfer in the Te complex suggests that Te is conducive for efficient electrical and atomic transport along the weak interaction path .…”
Section: Resultsmentioning
confidence: 99%